Bildbox! – Virtual Photo Booth that implements Augmented Reality - Leeson, Marchelno; Purnama, James; Galinium, Maulahikmah (Swiss German University, 2020)
The purpose of this research is to develop a self-service photo booth that implements augmented reality which is named as BildBox! where it allows the user of this product to try on different costumes virtually. There will be discussion on the Business Analysis that is conducted in this research to know the potential of the product as well as discussing the features that are implemented in the product. The development of the product’s software will be using Unity game engine and the depth image is taken by using Microsoft’s Kinect v2 depth camera. Aside from the discussions mentioned above, there will be also charts shown from the results of the surveys conducted. In the end, there will be a conclusion drawn from the survey results.